2020
DOI: 10.1371/journal.pone.0239370
|View full text |Cite
|
Sign up to set email alerts
|

Higher level of acute serum VEGF and larger infarct volume are more frequently associated with post-stroke cognitive impairment

Abstract: Background Serum vascular endothelial growth factor (VEGF) and infarct volume detected by brain imaging have been associated with stroke outcome. However, the relationship of these two variables with post-stroke cognitive impairment (PSCI) remains unclear. We aimed to investigate the association between acute serum VEGF levels and infarct volume with PSCI in ischemic stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 58 publications
2
17
0
Order By: Relevance
“…Twenty-three studies (N ¼ 6273) reported acute stroke features. [11][12][13][14][15][18][19][20][21][22][23][24]26,[28][29][30][31][32][33][34][35][36]38 Studies reported highly heterogeneous features which we grouped into location, size, number of lesions, and swelling (Supplement 10). Evidence was heterogeneous; however, in general, there were no clear predictors of PSD or PSCI.…”
Section: Acute Stroke Featuresmentioning
confidence: 99%
“…Twenty-three studies (N ¼ 6273) reported acute stroke features. [11][12][13][14][15][18][19][20][21][22][23][24]26,[28][29][30][31][32][33][34][35][36]38 Studies reported highly heterogeneous features which we grouped into location, size, number of lesions, and swelling (Supplement 10). Evidence was heterogeneous; however, in general, there were no clear predictors of PSD or PSCI.…”
Section: Acute Stroke Featuresmentioning
confidence: 99%
“…The possible explanation could be associated with the early VEGF concentration and the severity of stroke. The correlation between higher level of VEGF and the augmented infarct volume [ 29 ] could confirm this hypothesis, indicating that the release of higher amount of VEGF is essential for reducing the consequences of an increased-damage zone in the brain tissue, thus not leading to deleterious effects. However, to confirm that hypothesis, further investigations are required.…”
Section: Angiogenic Biomarker Of Stroke Recoverymentioning
confidence: 89%
“…Pordjohardjono et al showed that a higher VEGF level was linked with an almost 5-fold higher incidence of cognitive impairment. Interestingly, cognitive impairment was positively associated with larger infarct volume [ 29 ]. On the other hand, the impact of rehabilitation on VEGF concentration was determined in a study conducted by Ma et al Results showed that running significantly elevated the level of VEGF and MMP2, and augmented the absolute regional cerebral blood flow in the ischemic area 16 days after stroke in animal models, thus having beneficial effects on long-term recovery [ 30 ].…”
Section: Angiogenic Biomarker Of Stroke Recoverymentioning
confidence: 99%
“…The vascular endothelial growth factor (VEGF) family proteins, as well as other angiogenic factors, are also known to induce endothelial and neuronal remodeling after stroke ( Hayakawa et al, 2017 ). Levels of these proteins are elevated after ischemic insult in brain tissue and serum in rodent models and in humans ( Issa et al, 1999 ; Zhang et al, 2000 ; Prodjohardjono et al, 2020 ). However, few previous studies have evaluated whether changes in circulating angiogenic cells and proteins also occur in response to progressive and insidious cerebral SVD changes which commonly occur with advancing age.…”
Section: Introductionmentioning
confidence: 99%